Marine oligotrophication due to fine sediments and nutrient starvation caused by anthropogenic sediment and water retention in large rivers: the Nile damming case - Barak Herut; Tamar Guy-Haim; Ahuva Almogi-Labin; Helmut W. Fischer; Daniela Ransby; Amir Sandler; Timor Katz; Simona Avnaim-Katav (Frontiers in Marine Science, 2023)
In the last two centuries, human activities have radically reduced the transport of suspended sediment and water to marine systems, mainly in the northern hemisphere, while complete sediment retention has been reported for the Nile River after the construction of the Aswan High Dam (AHD). Here, we focused on changes in the inner-shelf sediments most exposed to the pre-AHD flood plume in the distal part of its littoral cell as a predictor of the ecological response to large river fragmentation. Substantial reductions in fine (15-40%) and increases in coarse (~8 fold) sediment accumulation rates, increases in CaCO 3 (~50%), decreases in autochthonous and total organic carbon (OC), and changes in the benthic foraminiferal assemblage toward more OC-sensitive species suggest an enhanced oligotrophication trend. The reduced nutrient fluxes and OC accumulation, and the coarsening of the shelf sediments inhibit the retention of “blue” carbon. Combined with fast climate warming and salinization, river fragmentation may have essential implications for the Eastern Mediterranean ecosystem via benthic oligotrophication processes.